Auxin, the organizer of the hormonal/environmental signals for root hair growth - Cho, Hyung-Taeg; Lee, Richard D. (Frontiers in Plant Science, 2013)
The root hair development is controlled by diverse factors such as fate-determining developmental cues, auxin-related environmental factors, and hormones. In particular, the soil environmental factors are important as they maximize their absorption by modulating root hair development. These environmental factors affect the root hair developmental process by making use of diverse hormones. These hormonal factors interact with each other to modulate root hair development in which auxin appears to form the most intensive networks with the pathways from environmental factors and hormones. Moreover, auxin action for root hair development is genetically located immediately upstream of the root hair-morphogenetic genes. These observations suggest that auxin plays as an organizing node for environmental/hormonal pathways to modulate root hair growth.